Isolated Talonavicular Joint Tuberculosis in a Child – Rare Location of Koch’s Bacillus: A Case Report - Mohd Faizan; Latif Z Jilani; Saifullah Khalid; Mazhar Abbas; Dilshad Anwar (Iranian Journal of Medical Sciences, 2017)
Tuberculosis of the foot is an uncommon entity and the reported incidence is 0.1% to 0.3%. The isolated tuberculosis of talonavicular joint is exceptionally rare. In tuberculosis of the foot and ankle, the presentation is usually nonspecific. The diagnosis of tuberculosis affecting foot is difficult, especially when it is isolated. In doubtful cases, diagnosis should be confirmed by histopathological examination. Unlike pulmonary Kochs, osteoarticular tuberculosis should be treated with antituberculous drugs for a longer duration, preferably for 18 months. We are reporting a case of a 9-year-old boy with tuberculosis of the isolated talonavicular joint and the diagnosis was suggested on plain radiography, which was further confirmed by histopathological examination. He was treated with first-line antitubercular drugs. A good recovery was seen following the commencement of anti-tuberculosis treatment. After two years of follow-up, he was pain-free and doing all of his routine activities. In tuberculosis of the foot, diagnosis is usually delayed or missed due to vague presentation.